Health disparities in preterm births - Brown, Judy; Chang, Xiaolin; Matson, Adam; Lainwala, Shabnam; Chen, Ming-Hui; Cong, Xiaomei; Casavant, Sharon G. (Frontiers in Public Health, 2023)
Introduction Black African American (B/AA) women have a 2-fold to 3-fold elevated risk compared with non-Hispanic White (W) women for preterm birth. Further, preterm birth is the leading cause of mortality among B/AA infants, and among survivors, preterm infant adverse health outcomes occur disproportionately in B/AA infants. Racial inequities in maternal and infant health continue to pose a public health crisis despite the discovery >100 years ago. The purpose of this study was to expand on reported preterm infant outcome disparities. A life-course approach, accumulation of lifelong stress, including discrimination, may explain social factors causing preterm birth rate and outcome inequities in B/AA mothers. Methods Anthropometric measures and clinical treatment information for 197 consented participants were milled from electronic health records across 4 years. The Neonatal Infant Stressor Scale was used to tally acute and chronic painful/stressful procedures. Neurobehavioral differences were investigated using the Neonatal Intensive Care Unit (NICU) Network Neurobehavioral Scale. Results B/AA mothers gave birth to preterm infants earlier than W mothers. NICU hospitalization stays were extended more than 2 weeks for the significantly smaller B/AA preterm infants in comparison to the age-matched W preterm infants. A higher number of chronic lifesaving procedures with demonstrated altered stress response patterns were recorded for B/AA preterm infants. Discussion This cross-sectional analysis of preterm birth rates and preterm infant developmental and neurodevelopmental outcomes are presented in the context of NICU stress and pain, with attendant implications for infant mortality and future health disparities. Preterm birth rate and outcome inequities further support the need to develop interventions and policies that will reduce the impact of discrimination and improve social determinants of health for Black, Indigenous, and other People of Color.